DAMPAK STRATEGI DIGITAL MARKETING PARIWISATA TERHADAP TINGKAT KEMISKINAN DI KABUPATEN PAMEKASAN: STUDY OF THE PARTICIPATION APPROACH - Masita, Yuliana; Ridialis, Alifah Rokhmah (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2024)
This research aims to analyze the impact of tourism digital marketing strategies on poverty levels in Pamekasan Regency, focusing on the community participatory approach. A qualitative method in the form of a case study was used to understand and analyze in depth the relationship between tourism digital marketing strategies and their impact on poverty levels in the region. Sampling was conducted using purposive sampling technique and data collection process through observation, interview, and documentary study. Data sources in this study include tourism-related stakeholders and the local community. Researchers also applied source triangulation techniques to assess the validity of the data. The results showed that tourism development that applies digital marketing strategies has a positive impact on increasing the number of tourist visits, besides that it can expand employment and increase community income which in turn can have a positive impact on reducing poverty levels. The role of the community in tourism development in Pamekasan Regency is as tourism managers, tourism management, and others. The results of this study are expected to provide insight into the importance of using and utilizing digital technology in tourism development so that it can have a positive impact on the local community.